DAYA HAMBAT EKSTRAK BIJI JINTAN HITAM (Nigella sativa Linn.) TERHADAP PERTUMBUHAN Candida albicans - Istiqomah, Siti Maryam; Aulung, Agus; Purwani, Luh Eka (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2015)
Infectious disease caused by candida is called Candidiasis and the species that mostly causes candidiasis is Candida albicans. Some fungal drugs have side effects that evoke discomfort, such as gastrointestinal disorde. Black cumin seed is traditional medicine that contains thymoquinoneas tha main indigredient that acts as an antifungal. This study was designed to study the antifungal inhibition activity of black cumin seed (N. sativa Linn) extract againts Candida albicans growth. This study used an experimental laboratory with the in vitro diffusion method in Sabouraund dextrose agar in order to observe and measure growth inhibition. Black cumin seed extract was obtained from Research Institute for Medicinal an Aromatic Plants (BALITRO) Bogor. The study showed that growth inhibition by the following concentration 100, 80, 60, 40, 20 and 10% with the mean of inhibition activity were 9.00; 4.83; 2.87; 2.49 and 0.19 mm. the data were analyzed by using alternative test and showed the probability score value of p < 0.05. It was concluded that black cumin seed extract had inhibition activity againts Candida albicans growth in vitro.